2002
DOI: 10.1016/s0735-1097(02)01786-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beraprost sodium, an oral prostacyclin analogue, in patients with pulmonary arterial hypertension: a randomized, double-blind, placebo-controlled trial

Abstract: Beraprost improves exercise capacity and symptoms in NYHA functional class II and III patients with PAH and, in particular, in those with primary pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
259
0
18

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 568 publications
(277 citation statements)
references
References 25 publications
0
259
0
18
Order By: Relevance
“…Following these studies and our initial experience [19] with beraprost regarding a group of patients with severe pulmonary hypertension – including 3 patients with distal CTEPH – we performed this prospective, case-controlled study to clarify whether beraprost produces clinical beneficial effect in distal CTEPH patients, comparable to what is seen in PAH patients [9, 20]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following these studies and our initial experience [19] with beraprost regarding a group of patients with severe pulmonary hypertension – including 3 patients with distal CTEPH – we performed this prospective, case-controlled study to clarify whether beraprost produces clinical beneficial effect in distal CTEPH patients, comparable to what is seen in PAH patients [9, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…The ALPHABET study [9] demonstrated that a 3-month treatment with beraprost improved exercise capacity in patients with PAH, mainly in idiopathic PAH (treatment effect +44 m), with a small, non-significant increase of cardiac index and no significant decrease in mean PAP. Similar results in effort tolerance were observed in the early phase (6 months) of a study in the US in which the median difference in the distance walked during 6 min was 31 m [20], but during the subsequent follow-up (9–12 months) the effort capacity declined close to the baseline in the beraprost group while in the placebo group continued to deteriorate over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seitdem sind große Fortschritte in der PAH-Therapie erzielt worden; in einer Reihe gut aufgebauter und durchgeführter klinischer Studien wurde die anhaltende Wirksamkeit verschiedener Therapien nachgewiesen, die bei verschiedenen PAH-spezifischen Anomalien ansetzen [13,14,15,16]. Zugleich sind die Behandlungen im Hinblick auf die Art der Anwendung einfacher geworden - an Stelle der kontinuierlichen intravenösen Gabe sind orale Einnahme und Inhalation getreten.…”
Section: Therapie Der Pulmonal-arteriellen Hypertonieunclassified
“…It provides improved exercise capacity and symptom relief, such as dyspnea at rest. Beraprost is associated with frequent side effects, such as headache, flushing, and diarrhea [26], which limit high-dose administration.…”
Section: Therapymentioning
confidence: 99%